Paper Dreams - Dragomoshchenko, A. (Arkadiĭ) (Book collections on Project MUSE., 2019)
Drawn from Hong Kong International Poetry Nights 2011, Paper Dreams is a chapbook of poetry by Arkadii Dragomoshchenko, accompanied by English and Chinese translations. Paper Dreams is also available along with the works of other internationally renowned poets in Words and the World (Twenty-volume Set). Selected poems from this volume are featured in the anthology Words and the World: International Poetry Nights in Hong Kong.